Case Report: Multi-cancer early detection utilizing blood-based genomics: Single-institution case series of novel cancer screening - Khare, Somya; Burton, Jason C.; De Asis, Francis; Mekonnen, Saron; Stewart-McLellan, Mason J.; Potts, Diana; Howard, Tiffani L.; Nabavizadeh, Nima (Frontiers in Oncology, 2025)
Purpose/Objective(s)Cancer screening continues to be a major challenge, with reliable tests only being available for very few cancers. Multi-cancer early detection (MCED) genomic tests are being developed that allow for blood-based screening of multiple cancers simultaneously. The PATHFINDER study was a multi-institution prospective cohort study in healthy participants over the age of 50 years (no cancer history, or history of treated cancer > 3 years prior), investigating the feasibility of the Galleri (GRAIL, LLC) cfDNA methylation MCED blood test. For participants in which the Galleri MCED test revealed methylation signatures indicative of cancer, predicted cancer signal origins were provided to the clinicians to assist with further diagnostic workup. Our institution was the highest accruing site nationally. Here, we describe our institutional test performance and provide informative case vignettes.Materials/MethodsUnder IRB approval, a retrospective chart review of participants enrolled in the PATHFINDER study was performed. Cancer risk factors, outcomes of tests and studies performed due to MCED signal positive, time to diagnostic resolution, and treatment outcomes were obtained from chart-review.ResultsFrom January 2020 to December 2020, our institution enrolled 1735 participants (26% of total study enrollment), 27 of which returned a signal positive for cancer suspicion (1.6%), and ultimately 12 diagnosed cancers (true positives) for a positive predictive value of 44%. Four of 12 were recurrent cancers in participants more than three years from cancer therapy. There were 15 signal positives without cancer diagnoses (false positives), with one patient receiving extensive work-up for possible uterus, breast or lung cancer origin. Six of 15 false positive results correlated to monoclonal B-cell lymphocytosis (chronic lymphocytic leukemia precursor). During the course of 12-month follow-up for signal negatives, 19 additional participants were diagnosed with a cancer (sensitivity: 39%, specificity: 99.1%).ConclusionOur institutional experience demonstrates the feasibility of MCED testing. Additional prospective randomized clinical trials are needed before widespread adoption. The information and data included in this manuscript was previously presented as a poster (e612 Poster Q&A Sessions) at the 2024 American Society for Radiation Oncology Annual Meeting.